Gomphonema rajaguruii sp. nov., a new diatom (Bacillariophyceae) species from the Western Ghats, India - Yogeshwaran, Murugesan; Kociolek, John Patrick; Karthick, Balasubramanian (Phytotaxa, 2023)
A new freshwater diatom species, Gomphonema rajaguruii sp. nov., is described from a wet wall at Mahabaleshwar, Western Ghats, Maharashtra, India. The new species is described based on light and scanning electron microscopy. Features that distinguish this new species from morphologically-similar species such as G. kallarense and G. lujanense include valve shape, which is broad at the centre and narrower near the poles, a distinctly lateral, undulate raphe system and costa-like striae, which are comprised of two rows of slit-like areolae. Although G. rajaguruii also resembles some taxa from the genus Gomphoneis, such as G. eriense and its close allies, it differs from them by lacking an axial plate. The description of G. rajaguruii sp. nov. increases the knowledge on the diatom diversity in the region.